Innovation of Education and Educational Innovations in Conditions of Modern Higher Education Institution - Halyna Mykhailyshyn; Oksana Kondur; Lesia Serman (Vasyl Stefanyk Precarpathian National University, 2018)
The article describes the different approaches to the interpretation of educational innovations and innovations in education. The modern labor market requires graduates ability to operate such technologies and knowledge that meet the needs of the information society, prepare young people for new roles in this society. It is necessary to distinguish between the concepts "educational innovations" and "innovations in education". Innovation in education is a broader concept than educational innovation. They include educational, scientific and technological, infrastructural, economic, social, legal, administrative and other innovations. Educational innovations are understood as a procedure or method of educational activity that differs significantly from established practice and is used to increase the level of efficiency in a competitive environment. Educational innovations include pedagogical innovation, scientific and methodological innovation, educational and technological innovation. It is substantiated that the education market is one of the most important elements of the national innovation system. Higher education institutions that have chosen an innovation-based development, become competitive leaders on the education market. The formation of new forms of education and the use of perfect controlling mechanisms at each educational institution will give the opportunity to create single educational space, which is able to meet the needs of society in quality education with specific opportunities of customers in the educational market. The main components of the innovation development of higher education institutions are determined.